Transfer Learning Based Prediction Model for Obstructive Sleep Apnea from Facial Depth Maps - K. Umarani, Mallapragada Saketha Ram (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Transfer Learning Based Prediction Model for Obstructive Sleep Apnea from Facial Depth Maps